2015
DOI: 10.1097/dad.0000000000000160
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Reactive Angioendotheliomatosis Secondary to the Administration of Trabectedin and Pegfilgrastim

Abstract: Diffuse dermal angiomatosis is a rare benign condition considered a variant of reactive angioendotheliomatosis, usually related to vascular disease such as arteriovenous fistula or severe peripheral vascular disease. The most frequent clinical manifestations range from a solitary erythematous patch to an indurated plaque that may ulcerate. A clinical case of a 60-year-old woman who developed generalized livedoid lesions 2 days after the administration of intravenous trabectedin and subcutaneous pegfilgrastim f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…After excluding cases with explicit unifocal involvement, involvement of both breasts, or un-reported location, 13 cases were found in the literature of DDA with multifocal involvement (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), as in our case (Table SI 1 ). Among them, 84.6% involved women, with mean age 58 years; 46.2% involved current smokers; and 46.2% featured atherosclerosis, as expected according to the review of Touloei et al (3) The thigh was the most common location, observed in 61.5% of cases.…”
Section: Multifocal Diffuse Dermal Angiomatosis: a Reflection Of High Cardiovascular Riskmentioning
confidence: 84%
“…After excluding cases with explicit unifocal involvement, involvement of both breasts, or un-reported location, 13 cases were found in the literature of DDA with multifocal involvement (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), as in our case (Table SI 1 ). Among them, 84.6% involved women, with mean age 58 years; 46.2% involved current smokers; and 46.2% featured atherosclerosis, as expected according to the review of Touloei et al (3) The thigh was the most common location, observed in 61.5% of cases.…”
Section: Multifocal Diffuse Dermal Angiomatosis: a Reflection Of High Cardiovascular Riskmentioning
confidence: 84%
“…8 Several cases of RAE have been connected with antiphospholipid antibody syndrome and adverse drug reaction. 4,[9][10][11][12] Furthermore, RAE has been observed in adenopathy and extensive skin patch overlying a plasmacytoma syndrome, an early manifestation of polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, and skin changes syndrome, which rapidly progresses without treatment and can become life-threatening. 13,14 Angiomatosis with cryoproteins, also known as angiopericytomatosis, is an infrequently recognized variant of RAE with few published cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A wide spectrum of predisposing comorbid conditions have been associated with DDA in other body parts than the breast, such as advanced atherosclerotic vascular disease [ 6 , 7 , 8 , 9 , 10 ], iatrogenic arteriovenous fistula in the setting of chronic hemodialysis [ 11 , 12 ], monoclonal gammopathy [ 13 , 14 ], and the administration of trabectedin and pegfilgrastim in the context of liposarcoma in 1 case [ 15 ]. Cardiovascular risk factors, atherosclerotic vascular disease, and monoclonal gammopathy have also been described in association with DDAB.…”
Section: Discussionmentioning
confidence: 99%